Postoperative Urinary Retention after Pediatric Orthopedic Surgery - Mohan V. Belthur; Ian M. Singleton; Jessica D. Burns; M'hamed H. Temkit; Thomas J. Sitzman (MDPI AG, 2022)
Purpose: This study aims to describe the incidence of postoperative urinary retention among pediatric patients undergoing orthopedic surgery and identify risk factors. Methods: The Pediatric Health Information System was used to identify children aged 1-18 years who underwent orthopedic surgery. Collected from each patient's record were demographic information, principal procedure during hospitalization, the presence of neurologic/neuromuscular conditions and other complex chronic medical conditions, the total postoperative length of stay, and the presence of postoperative urinary retention. Results: The overall incidence of postoperative urinary retention was 0.38%. Children with complex chronic neuromuscular conditions (OR 11.54 (95% CI 9.60-13.88), p = < 0.001) and complex chronic non-neuromuscular medical conditions (OR 5.07 (95% CI 4.11-6.25), p ≤ 0.001) had a substantially increased incidence of urinary retention. Surgeries on the spine (OR 3.98 (95% CI 3.28-4.82, p ≤ 0.001) and femur/hip (OR 3.63 (95% CI 3.03-4.36), p ≤ 0.001) were also associated with an increased incidence. Conclusions: Children with complex chronic neuromuscular conditions have a substantially increased risk of experiencing postoperative urinary retention. Complex chronic non-neuromuscular medical conditions and surgeries to the spine, hip, and femur also carry a notably increased risk.